Synthesis of lactic acid from sugar palm trunk waste (Arenga pinnata): Preliminary hydrolysis and fermentation studies (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Erliana WH, Widjaja T, Altway A, Pudjiastuti L. 2020. Synthesis of lactic acid from sugar palm trunk waste (Arenga pinnata): Hydrolysis and fermentation studies. Biodiversitas 21: 2281-2288. The increasing problems of global energy and the environment are the main reasons for developing products with new techniques through green methods. Sugar palm trunk waste (SPTW) has potential as agricultural waste because of its abundant availability, but it is not used optimally. This study was aimed to determine the effect of various microorganisms on increasing lactic acid production by controlling pH and temperature conditions in the fermentation process. SPTW contains 43.88% cellulose, 7.24% hemicellulose, and 33.24% lignin. The lignin content in SPTW can inhibit reducing sugar formation; the pretreatment process should remove this content. In the study, the pretreatment process was conducted using acid-organosolv. In the acid pretreatment, 0.2 M H2SO4 was added at 120oC for 40 minutes; organosolv pretreatment using 30% ethanol (v/v) at 107oC for 33 minutes was able to increase cellulose content by 56.33% and decrease lignin content by 27.09%. The pretreatment was followed by an enzymatic hydrolysis process with a combination of commercial cellulase enzymes from Aspergillus niger (AN) and Trichoderma reesei (TR), with variations of 0:1, 1:0, 1:1, 1:2 and 2:1. The best reducing sugar concentration was obtained with an AN: TR ratio of 1:2 to form reducing sugar from cellulose. Subsequently, lactic acid fermentation was carried out using lactic acid bacteria at 37oC and pH 6 incubated for 48 hours. The highest lactic acid concentration (33.292 g/L) was obtained using a mixed culture of Lactobacillus rhamnosus and Lactobacillus brevis to convert reducing sugar become lactic acid.
Keywords: acid-organosolv pretreatment, cellulase enzyme, lactic acid, lactic acid bacteria, sugar palm trunk waste.